Correlates of HIV and STI testing among Latino men who have sex with men in New York City. Issue 6 (2nd June 2016) - Spadafino, Joseph T.; Martinez, Omar; Levine, Ethan C.; Dodge, Brian; Muñoz-Laboy, Miguel; Fernandez, M. Isabel
ABSTRACT: We assessed the extent to which sociodemographic, personal, and behavioral factors are associated with human immunodeﬁciency virus/sexually transmitted infection (HIV/STI) testing among a diverse group of Latino men who have sex with men (MSM) in New York City. The triangulation approach was used to synthesize data from 176 MSM who completed an in-person or phone questionnaire about substance use, alcohol consumption, sexual behaviors, and HIV/STI testing history and 40 participants who participated in focus groups. Correlates of testing significant in univariable analyses ( p  < .05) were entered into multivariable logistic regression models. Over half (57.9%) of study subjects tested for HIV in the previous 12 months and 60.2% tested for STIs in the previous 12 months. Age and education were positively correlated with HIV testing in multivariable analysis. No significant correlates of STI testing were identified. Spanish-speaking only subjects were less likely to get tested for HIV and STI; however, this association was not significant. Our study demonstrates the need for further study of predictors of STI testing as well as the potential role of language barriers and education in routine testing for HIV. Social and behavioral factors may intensify these obstacles. Future research and interventions should address the role of language barriers and perceived issues of immigration status in the decision to get tested.